2019
DOI: 10.1002/cre2.208
|View full text |Cite
|
Sign up to set email alerts
|

A small number of residual teeth after the mandibular resection of oral cancer is associated with titanium reconstruction plate exposure

Abstract: ObjectiveReconstruction plates are used to treat patients with a segmental mandibular defect after oral cancer surgery. Reconstruction plate failure analysis has rarely focused on occlusion, which conducts a mechanical force to the mandible and the plate. To determine the prognostic factors, we retrospectively evaluated patients who underwent reconstruction of a mandibular segmental defect with a reconstruction plate and assessed the number of residual paired teeth.Material and MethodsFrom among 390 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In defect size quartile three, between 61 and 90 mm, most frequent complications were exposed plates in the healing process. The literature indicates that a low number of residual teeth is a significant prognostic factor for reconstruction plate loss (53). The results of this study are consistent with the literature as bone loss in the 61-90-mm range is associated with loss of dentition.…”
Section: Discussionsupporting
confidence: 91%
“…In defect size quartile three, between 61 and 90 mm, most frequent complications were exposed plates in the healing process. The literature indicates that a low number of residual teeth is a significant prognostic factor for reconstruction plate loss (53). The results of this study are consistent with the literature as bone loss in the 61-90-mm range is associated with loss of dentition.…”
Section: Discussionsupporting
confidence: 91%
“…5 A–C. After 12 weeks of implantation, macroscopic views of the subcutaneous implantation sites revealed that the larger amount of ECM in osteoblastic BMSC sheets or produced during the coculturing of BMSCs and PT scaffolds in osteogenic medium markedly increased the biocompatibility of PT scaffolds and decreased the risk of metal exposure in PT/HC and PT/CS groups, which commonly occurs in patients who received titanium alloy plate for the immediate repair of postoperative defects after the removal of mandibular malignant tumors [ 42 ]. In contrast, the implanted PT scaffolds in the PT/LC group were almost completely exposed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Complications predominantly include fractures, instability, extrusion, and rejection of implants. Furthermore, custom-made implants are associated with consequential financial costs [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%